ID: 200. Issue 1 (November 2015) - Clement, Mathew; Stacey, Maria A.; Marsden, Morgan; Jones, Gareth; Jones, Simon A.; Humphreys, Ian R.
<x xml:space="preserve">Abstract</x> Human cytomegalovirus (HCMV) is an important viral pathogen in the immune suppressed and immunologically immature. HCMV encodes a functional homologue of the immune modulatory cytokine interleukin-10 (IL-10), implying the importance of this pathway in moderating antiviral immunity. Using the murine model of CMV infection, we now report that virus-specific CD4 T-cells produce IL-10 in response to infection in an epitope-restricted manner. Using CD4creIL-10flox mice we demonstrated that CD4+ cell-derived IL-10 promoted viral persistence by inhibiting antiviral T-cell responses. We sought to investigate the governing factors of IL-10 production by CD4+ T-cells during infection. We found that IL-10 production by CD4+ T-cells during the early stages of MCMV infection was driven by IL-27. Using WSX1−/− (IL-27R−/−) mice, we found that impaired early IL-10 expression by virus-specific T cells in the periphery permits a greater functional anti-viral mucosal response during virus chronicity. Thus specific targeting and abrogation of IL-10-producing CD4+ T-cells via inhibition of IL-27R signalling will enable the development of effective anti-CMV T-cell immunity in mucosal surfaces.